Cartografias cotidianas: acompanhando a implantação de uma residência inclusiva para jovens e adultos com deficiência intelectual - Mello, Barbara Cristina [UNIFESP] (2015)
The study aimed using the tool cartographies everyday to support an implant residence inclusive for youth and adults with intellectual disabilities in baixada santista.